ANGIOGRAPHIC STUDY OF THE NORMAL CORONARY ARTERY IN PATIENTS ATTENDING ULAIMANI CENTER FOR HEART DISEASES - Shukri, Imad Ghanem; Hawas, Jawad Mohammed; Karim, Shilan Huseein; Ali, Issraa Khalil M. (European Scientific Journal, ESJ, 2014)
Background and aim :There is no available data on normal coronary artery dimensions among Iraqi Kurdish population (Sulaimani region), so that our aim is to study the normal dimensions of the coronary artery segments during life by using quantitative coronary angiography with reference to dominancy and variations and possibly to help interventional cardiologist and cardiac surgeon. Methods:Between February 2009 to June 2009, 88 patients underwent quantitative coronary angiography for evaluation of symptoms of ischemic heart disease and were found to have no coronary artery disease from the sample size. Results: The diameter of the coronary arteries were larger in male subjects than females with significant p-value for LMCA, proximal LAD, LCx and RCA regarding proximal RCA also was larger among male but statistica-lly was non significant .The diameter of the coronary arteries in Kurdish population were similar to Caucasians and white but greater than that of Indians.Conclusion:In general males has larger coronary artery diameter than females, the mean diameter was similar to that reported in Caucasians and white and larger than Indians.